Effect of pre-operative 40 mg oral methylprednisolone on post- odontectomy facial swelling, intraoral redness, pain and level of TNF-α - Harpindo Yusa; Cahya Yustisia Hasan; Bambang Dwirahardjo (Majalah Kedokteran Gigi Indonesia, 2022)
Odontectomy is the surgical removal of teeth by making a mucoperiosteal flap and reducing the jawbone. This procedure is likely to cause injury and damage to soft and hard tissues, stimulate inflammatory responses, and generate release of proinflammatory cytokines, one of which is TNF- ɑ, resulting in the facial swelling, intraoral redness, and pain. This study was aimed at observing effects of 40 mg methylprednisolone, administered 1 hour before odontectomy on facial swelling, intraoral redness, and pain and level of TNF-ɑ after odontectomy. The randomized placebo-control trial study involved 24 subjects who underwent odontectomy at the Oral Surgery and Maxillofacial clinic of Prof. Soedomo Dental Hospital, Universitas Gadjah Mada. To comply with the inclusion criteria, the subjects were divided into placebo group (12 patients) and methylprednisolone group (12 patients). The observation of facial swelling, intraoral redness, pain (VAS) and level of TNF-ɑ (ELISA) was done before odontectormy, H+1 (24 hours after odontectomy) and H+3 (72 hours after odontectomy). The data gathered were analyzed using Repeated Measures ANOVA and post-hoc Bonferroni (p < 0.05). The results showed that those administered with methylprednisolone an hour before odontectomy experienced less postoperative facial swelling (p = 0.000), a lower score of intraoral redness (p = 0.000), a lower score of pain (p = 0.000) and a lower level of TNF-ɑ (p = 0.000) compared to the placebo. The changes in TNF-α showed the strongest correlation with the changes in postoperative pain and intraoral redness compared with facial swelling. Oral administration of 40 mg methylprednisolone an hour before odontectomy is more effective in reducing facial swelling, intraoral redness, pain and level of TNF-ɑ following odontectomy of mandibular third molar compared with the placebo.